Immune status improvement in piglets through the use of interferon-containing products during specific prevention of porcine pleuropneumonia - A. G. Shakhov; L. Yu. Sashnina; V. A. Prokulevich; Yu. Yu. Vladimirova; M. I. Adodina (Ветеринария сегодня)
Specific prevention is one of the most effective methods for the control of infectious diseases causing considerable economic damage to commercial pig farms, among which is porcine pleuropneumonia. In order to improve the effectiveness of preventive vaccination, various immunomodulators that differ in their origin and mechanism of action are used. The paper presents the results of the study of the effect of such products as biferon-S and prostimul containing species-specific recombinant interferons on the immune status of piglets during specific prevention of porcine pleuropneumonia. Tests were carried out in clinically healthy 30–35-day-old piglets immunized with Ingelvac® APPX vaccine (Boehringer Ingelheim Vetmedica GmbH, Germany). It was found that the use of biferon-S and prostimul together with the vaccine administration is accompanied by immune status improvement in the animals, which is manifested as an increase, in comparison with vaccinated animals that received no interferon-containing products (base case), in serum levels of γ-globulins – by 34.6 and 53.7% (in case of prostimul and β-globulins – by 10.1%), total immunoglobulins – by 32.8 and 37.8%, large circulating immune complexes – by 37.5 and 52.6%, a less significant increase in the levels of small complexes and, as a result, pathogenicity coefficient reduction by 5.4 and 12.4%, respectively. Tests for post-vaccination immunity levels in piglets showed a 3.8-fold increase in the levels of specific antibodies against the antigen of porcine pleuropneumonia agent, and in case of the vaccine administration in combination with biferon-S and prostimul – a 4.0-fold and 4.9-fold increase, respectively. The use of prostimul was accompanied by a more considerable improvement of immune status in the piglets, and this is attributable to the fact that vitamins А, Е and С, which have antioxidant properties and improve the effectiveness of interferons, natural resistance and specific immunity, are included in its composition in addition to recombinant type 1 cytokine.